REPRESENTATION OF EXPERIENCE IN SUSILOBAMBANG YUDHOYONO’S SPEECH - Rahmat Huda (Universitas Muhammadiyah Tapanuli Selatan, 2018)
The study presents a research conducted of Experiential Function in Susilo Bambang Yudhoyono’s speech at the Asia Pacific Regional Conference of Open Government Partnership (OGP) which hold in Nusa Dua Bali. The main objective found the dominant pattens of representation of experience formed by transitivity (process, participant and circumtance) and described of situational contexts (arena, participant’s characteristics and semantic domain). It presented a qualitative design dealing with quantifiable (numeric) mode. The source of the data was taken from the opening speech of Susilo Bambang Yudhoyono on May 6, 2014. The data were collected by applying documentary technique. The data analysis found out the findings that there were five types of process from six types of process (material, mental, relational, behavioural, verbal and existential). The patterns of each process were different from others, namely material patterns 59 (55.67%), mental 19 (17.92%), relational; identification 3 (2.83%), attribution 10 (9.43%), possession 7 (6.60%), verbal 5 (4.71%) and exsistential 3 (2.83%). The percentage shows that the dominant patterns are formed by material process. Whereas, the behaviuoral pattern related to pshyological and psychological did not find in the speech. Meanwhile, the context of situation of the speech tend to the field and dominated by arena or social activity which refers to the location where social activities were performed, especially [+institutionalized]